Search for Microorganisms in Men with Urologic Chronic Pelvic Pain Syndrome: A Culture-Independent Analysis in the MAPP Research Network - Nickel, J. Curtis; Stephens, Alisa; Landis, J. Richard; Chen, Jun; Mullins, Chris; van Bokhoven, Adrie; Lucia, M. Scott; Melton-Kreft, Rachael; Ehrlich, Garth D (The Journal of urology, 2015)
Purpose We used next-generation, state-of-the-art, culture independent methodology to survey urine microbiota of males with urologic chronic pelvic pain syndrome and control participants enrolled in the MAPP Network to investigate a possible microbial etiology. Materials and Methods Male patients with urologic chronic pelvic pain syndrome and matched controls were asked to provide initial, midstream and post-prostatic massage urine specimens. Specimens were analyzed with Ibis T-5000 Universal Biosensor technology to provide comprehensive identification of bacterial and select fungal species. Differences between urologic chronic pelvic pain syndrome and control study participants for the presence of species or species variation in a higher taxonomic grouping (genus) were evaluated using permutational multivariate analysis of variance and logistic regression. Results Initial and midstream urine specimens were obtained from 110 (post-prostatic massage urine in 67) participants with urologic chronic pelvic pain syndrome and 115 (post-prostatic massage urine in 62) controls. Overall 78, 73 and 54 species (42, 39 and 27 genera) were detected in initial, midstream and post-prostatic massage urine specimens, respectively. Mean (SD) initial, midstream and post-prostatic massage urine species count per person was 1.62 (1.28), 1.38 (1.36) and 1.33 (1.24) for cases, and 1.75 (1.32), 1.23 (1.15) and 1.56 (0.97) for controls, respectively. Overall species and genus composition differed significantly between participants with urologic chronic pelvic pain syndrome and controls in initial stream urine (p=0.002 species level, p=0.004 genus level), with Burkholderia cenocepacia overrepresented in urologic chronic pelvic pain syndrome. No significant differences were observed at any level in midstream or post-prostatic massage urine samples. Conclusions Assessment of baseline culture-independent microbiological data from male subjects enrolled in the MAPP Network has identified overrepresentation of B. cenocepacia in urologic chronic pelvic pain syndrome. Future studies are planned to further evaluate microbiota associations with variable and changing urologic chronic pelvic pain syndrome symptom patterns.